Pengaruh Kesadaran Halal Dan Harga Produk Terhadap Permintaan Ramen di Kota Medan - Elvina Riska; Rahmi Syahriza; Nurul Inayah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Halal awareness is the level of awareness of a muslim to use products that are eaten, drunk, or used based on the principles taught by Islam. In Islam, halal refers to all products that are considered halal through various aspects, from production, until the product is delivered to the consumer. The demand for a product is inseparable from price, which is a factor that attracts consumer attention because it is a consideration for consumers in making purchases. Halal awareness also has a positive impact on product purchases. This study aims to analyze the influence of halal awareness and price on the demand for ramen in Medan City. This study is a quantitative descriptive study, involving 100 respondents from Medan City as the research sample. This study aims to map the problem model objectively and provide a systematic and accurate description. The goal is to analyze and reveal facts from a specific object by distributing questionnaires to research respondents, which are then analyzed using a Likert scale using software called SPSS. The results of the study indicate that there is a positive and significant influence of halal awareness on the demand for ramen. This has led to an increasing understanding of the Muslim community regarding the concept and principles of halal before making a purchase of the desired product. On the other hand, there is also a positive and significant effect between price and demand for ramen. This occurs because price factors, including affordability and the appropriateness of price and benefits, are important considerations for consumers when making a purchase. Overall, halal awareness and price have a positive and significant effect on ramen demand in Medan.